Multi-phase, multi-ethnic GWAS uncovers putative loci in predisposition to elite sprint and power performance, health and disease - Wang, G.; Fuku, N.; Miyamoto-Mikami, E.; Tanaka, M.; Miyachi, M.; Murakami, H.; Mitchell, B. D.; Morrison, E.; Ahmetov, I. I.; Sportgene Research Group; Generozov, E. V.; Filipenko, M. L.; et al. (Biology of Sport, 2025)
The genetic underpinnings of elite sprint and power performance remain largely elusive. This study aimed to identify genetic variants associated with this complex trait as well as to understand their functional implications in elite sprint and power performance. We conducted a multi-phase genome-wide association study (GWAS) in world-class sprint and power athletes of West African and East Asian ancestry and their geographically matched controls. We carried out genotype imputation, replications for the top GWAS signal rs10196189 in two European cohorts, and gene-based and tissue-specific functional network analyses. For the first time, we uncovered the G-allele of rs10196189 in the Polypeptide N Acetylgalactosaminyltransferase 13 (GALNT13) being significantly associated with elite sprint and power performance (P = 2.13E-09 across the three ancestral groups). Moreover, we found that GALNT13 expression level was positively associated with the relative area occupied by fast-twitch muscle fibers in the vastus lateralis muscle. In addition, significant and borderline associations were observed for BOP1, HSF1, STXBP2, GRM7, MPRIP, ZFYVE28, CERS4, and ADAMTS18 in cross-ancestry or ancestry-specific contexts, predominantly expressed in the nervous and hematopoietic systems. From the elite athlete cohorts, we further identified thirty-six previously uncharacterized genes linked to host defence, leukocyte migration, and cellular responses to interferon-gamma, and four genes - UQCRFS1, PTPN6, RALY and ZMYM4 - associated with aging, neurological conditions, and blood disorders. Taken together, these results provide new biological insights into the genetic basis of elite sprint and power performance and, importantly, offer valuable clues to the molecular mechanisms underlying elite athletic performance, health and disease.